Pengembangan Media E-book untuk Meningkatkan Literasi Sains Siswa Kelas 5 Pada Materi Perubahan Benda - Atep Sujana; Enjang Yusuf Ali; Aliffia Annissa Firdaus (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to determine the development of e-book media to improve fifth-grade students' science literacy on the changes in matter topics. This study is motivated by the issue of low science literacy among the students. Science literacy can be performed properly since it is supported by the appropriate selection of learning media. This study was conducted at one of the public elementary schools in the Ciparay Subdistrict of Bandung Regency, using a descriptive essay test as the instrument. Meanwhile, the study used the Design & Development method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model approach. The analysis stage included analyzing the content of the material, users, hardware, and software. The design stage included designing the entire design using a flowchart. The development stage included developing the entire e-book media design, which was validated by media and material experts, and achieving an average result of 94% in the “Highly Feasible” category. In the implementation stage, product testing of the e-book media was conducted on 30 students and 3 teachers, obtaining an average result of 87%, categorized as 'Very Good'. Then, for the improvement of fifth-grade students’ science literacy, specifically on the topic of changes in matter, the average pretest score obtained was 39.87. After using the e-book, the average post-test score increased to 62.46. In the evaluation stage, the experts refined the design and appearance of the e-book media according to user needs. E-book has met the needs of the school in the teaching and learning process.